Mechanisms of fluorescence decays of colloidal CdSe–CdS/ZnS quantum dots unraveled by time-resolved fluorescence measurement. Issue 41 (1st October 2015) - Xu, Hao; Chmyrov, Volodymyr; Widengren, Jerker; Brismar, Hjalmar; Fu, Ying
Abstract : The fluorescence decay spectrum of colloidal CdSe-based quantum dots is characterized by energy relaxation and radiative recombination of photoexcited excitons. Abstract : By narrowing the detection bandpass and increasing the signal-to-noise ratio in measuring the time-resolved fluorescence decay spectrum of colloidal CdSe–CdS/ZnS quantum dots (QDs), we show that directly after the photoexcitation, the fluorescence decay spectrum is characterized by a single exponential decay, which represents the energy relaxation of the photogenerated exciton from its initial high-energy state to the ground exciton state. The fluorescence decay spectrum of long decay time is in the form of β / t 2, where β is the radiative recombination time of the ground-state exciton and t is the decay time. Our findings provide us with a direct and quantitative link between fluorescence decay measurement data and fundamental photophysics of QD exciton, thereby leading to a novel way of applying colloidal QDs to study microscopic, physical and chemical processes in many fields including biomedicine.